Lithuanian resultatives in the context of neighbouring Slavic languages - Riaubienė, Benita (Lietuvių kalba, 2015)
Resultative secondary predicates, or resultatives, express the state of a participant of an event as a result of the action denoted by a verb. On the other hand, resultatives bear a semantic relation to the main predicate as well. Due to this fact and due to their encoding by adverbs, Lithuanian resultatives are superficially similar to adverbials. This might be the reason why resultative secondary predicates have for a long time remained unnoticed in Lithuanian linguistics. A boundary between resultatives proper and the so-called pseudo-resultatives has to be drawn in order to get an accurate description of the phenomenon. Pseudo-resultatives are constructions semantically and/or formally resembling resultatives proper but lacking the causative relation between the primary and secondary predications; they can, at best, be treated as belonging to the periphery of the domain of resultatives. As the data of Lithuanian, Russian and Polish resultatives reveals, the three languages share some common features. First, all of them encode the basic result component by means of verbal prefixes, while the secondary predicates only specify the result that is already implied by a verb. Secondly, all languages make use of prepositional phrases including the preposition to as one of the strategies for encoding resultative secondary predication. Besides, Lithuanian and Polish, unlike Russian, generally avoid resultatives based on intransitive verbs (except optionally transitive verbs like eat and drink). However, there are major differences as regards the distribution of to-PPs in the languages. In Lithuanian the use of to-PPs is determined by the lexical aspect of a verb: accomplishments usually do not combine with resultative prepositional phrases, while activities do. Another factor operates in Russian and Polish: to-PPs are used with verbs that emphasize a process leading up to the resulting property, while the verbs that highlight the resulting property as such take resultatives encoded by other strategies. In the former case the resulting property is accumulated as the action proceeds: to load the cart full, to eat oneself full, etc. In the latter case a verb usually implies a bundle of finer-grained properties for which the values have to be set in advance: to paint the car red/green/blue, to cook the egg hard/soft, etc. The difference between the accumulated property and the pre-set value can also be formulated in terms of goal and manner: the accumulated property parallels progressing towards the goal, while the pre-set value resembles the manner in which an action is carried out. Polish and Russian, in turn, also show a difference: the former distinguishes two types of resultatives (expressing a pre-set value and expressing an accumulated property), while the latter in addition has a special type of marking for resultatives like to wipe the table clean which are intermediate between the preset-value and the accumulated-property types.
Keywords: resultatives; action; predicate; pseudo-resultatives; causative